Gerakan Pemuda Era Reformasi: (Studi Kasus Aksi "Indonesia Gelap" di Jember dalam Perspektif Charles Tilly) - Gesti Setyo Hadi; Ayu Firza Noviyanti; Muhammad Imam Al Fikri; Muhammad Rizky Al Zam Zami (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The Dark Indonesia Action is a symbol of the resistance and struggle of the youth in fighting for justice. The action not only took place in Jakarta but also in several regions including in Jember Regency, precisely in front of the DPRD building. The action, which was dominated by students, took place peacefully and orderly. Participants compactly used all-black clothes as a form of representation for the realization of one hundred days of leadership of the elected president. This research aims to analyze the dark Indonesia action that occurred in Jember using the social movement theory proposed by Charles Tilly, specifically through three main concepts, namely, repertoire, campaign, and WUNC (worthiness, unity, numbers, commitment) storefront. This research uses a qualitative method with a phenomenological approach that focuses on the direct experience of individuals involved in the action. The results showed that the participants of the Indonesia Gelap action in Jember had fulfilled the three concepts proposed by Tilly. Thus, the Dark Indonesia action can be understood as a form of organized social movement that has structures, symbols, and a strong collective spirit in fighting for the aspirations of justice in the community.